1997
DOI: 10.1074/jbc.272.35.21831
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of ATP-induced Ca2+ Signaling in HL-60 Cells Is Mediated by Protein Kinase A- and C-mediated Changes in Capacitative Ca2+ Entry

Abstract: Extracellular ATP evokes many physiological effects such as platelet aggregation, neurotransmission, inflammation, and muscle contraction in numerous cell types (1). These various effects of ATP are mediated by plasma membrane P 2 purinergic receptors (2). Six subtypes of P 2 purinergic receptors, P 2X , P 2Y , P 2D , P 2T , P 2Z , and P 2U , were identified in pharmacological and functional studies and supported by cloning data (3 -binding proteins are also involved in buffering the cytosolic Ca 2ϩ concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…The opposing regulatory actions of PKA and PKC could provide the cells with an elaborate and highly responsive regulation of capacitative calcium entry in the achievement of calcium homeostasis. Recently, we observed that the elevation of intracellular calcium level elicited by the stimulation of ATP receptors which are coupled to adenylyl cyclase and PLC was modulated in a feedback mode with regulation of capacitative calcium entry by subsequent activation of PKA and PKC [26]. Our present study also suggests that concomitant or sequential activation of various receptors linked to adenylyl cyclase or PLC may very well affect intracellular calcium homeostasis and result in different physiological responses.…”
Section: Discussionmentioning
confidence: 51%
“…The opposing regulatory actions of PKA and PKC could provide the cells with an elaborate and highly responsive regulation of capacitative calcium entry in the achievement of calcium homeostasis. Recently, we observed that the elevation of intracellular calcium level elicited by the stimulation of ATP receptors which are coupled to adenylyl cyclase and PLC was modulated in a feedback mode with regulation of capacitative calcium entry by subsequent activation of PKA and PKC [26]. Our present study also suggests that concomitant or sequential activation of various receptors linked to adenylyl cyclase or PLC may very well affect intracellular calcium homeostasis and result in different physiological responses.…”
Section: Discussionmentioning
confidence: 51%
“…Mn 2ϩ is a good surrogate for Ca 2ϩ ions in these kind of experiments, since it is not pumped out of the cells. Thus, it can be used as a selective tracer for Ca 2ϩ influx (22). As shown in Fig.…”
Section: Overexpression Of Plc-␦1 In Pc12-d1mentioning
confidence: 99%
“…ATP and UTP activated superoxide formation in HL-60 promyelocytic leukaemic cells [440] and ATP also increased [Ca 2+ ] i in these cells [441,442] probably via P2Y 2 receptors [443,444]. Reduced proliferation was produced by ATP and UTP in both HL-60 promyelocytic and U937 promonocytic human cell lines [445], perhaps via A 3 receptors [446].…”
Section: Lymphocytic Leukaemiamentioning
confidence: 99%